Solid State Physics Principles and Modern Applications - Quinn, John J. (UNITEXT for Physics,, 2018)
This book provides the basis for a two-semester graduate course on solid-state physics. The first half presents all the knowledge necessary for a one-semester survey of solid-state physics, but in greater depth than most introductory solid state physics courses. The second half includes most of the important research over the past half-century, covering both the fundamental principles and most recent advances. This new edition includes the latest developments in the treatment of strongly interacting two-dimensional electrons and discusses the generalization from small to larger systems. The book provides explanations in a class-tested tutorial style, and each chapter includes problems reviewing key concepts and calculations. The updated exercises and solutions enable students to become familiar with contemporary research activities, such as the electronic properties of massless fermions in graphene and topological insulators.